An An Analysis of Lif-Conditions in Samuel Beckett’s Happy Days and the Covid-19 Pandemic: Similarities and Differences - Alkurdi, Firas (International Journal of Language and Literary Studies, 2022)
The Second World War caused long-term destruction to human life in the countries involved. As a result, life at that time was severely affected by many economic, educational, and social factors that exceeded the physical disability and psychological trauma. Likewise, the COVID-19 pandemic has created a situation of human disability in terms of diverse conditions of life. This paper studies the similarities and differences between human life conditions during the Second World War and the pandemic time of COVID-19. This paper relies on Beckett’s Happy Day to reflect the living conditions caused by the Second World War. Parallelly, references to international reports and articles about COVID-19 are made to depict the life conditions created since the spread of the virus. Hence, this study tries to answer the hypothetical question of how similar human life during the COVID-19 pandemic time is to that depicted by Samuel Beckett represents in his play Happy Days. This paper is restricted to the psychological consequences of pandemics. However, as plague literature resurrects, relationships between pandemics and human living conditions are invited to the table of academia. Other pandemics in different times in history, other types of consequences, and diverse literary works are highly recommended to be the subject matter of researchers worldwide.